The Development of Public Interest in Sharia-Compliant Investments in Indonesia - Dwiarnanto, Andry; Dovristyadi, Nugrah (Mandalika Law Journal, 2025)
Investment is a solution that can be used to manage personal finances. One of the financial products that has gained considerable popularity is Sharia-compliant stocks. However, recent cases of fraudulent investments have also involved several Indonesian influencers. Certainly, the victims had underlying factors that led them to become entangled in fraudulent investment schemes, which subsequently influenced their interest in investing. Therefore, this study aims to examine the effect of investment knowledge, Sharia online trading systems, and motivation on investment interest in Sharia-compliant stocks in Indonesia. Investment is part of a system used to manage financial resources. One of the most popular financial products within this system is Sharia-compliant stocks. Nevertheless, as explained above, many investment schemes direct investors toward products that lack a clear legal basis and official legality. Victims of such schemes are influenced by various factors that lead to their interest in investing. Hence, this research seeks to analyze the influence of investment knowledge, Sharia online trading systems, and motivation on interest in investing in Sharia-compliant stocks through investment galleries. The level of interest among the Indonesian public in investment products has reached a relatively high level, indicating growing awareness of investment instruments, particularly stock-based investments. In general, stocks are traded on the Indonesia Stock Exchange, where every listed company has clear legal certainty and is supervised by authorized regulatory institutions.